Global fibrinolytic activity, PAI-1 level, and 4G/5G polymorphism in thai children with arterial ischemic stroke - Natesirinilkul,R. (W.B. Saunders Ltd, 2015)
© 2014 by National Stroke Association. Background: Prolonged euglobulin clot lysis time (ECLT) and increased level of plasminogen activator inhibitor-1 (PAI-1) were reported to be risk factors of arterial ischemic stroke (AIS) by some studies; however, these findings were not supported by other studies. The objective of this study was to determine the association of ECLT, PAI-1 level, and polymorphisms of 4G and 5G of PAI-1 gene to the development of AIS in Thai children. Methods: This study included patients aged 1-18 years old. Diagnosis of AIS was confirmed by imaging study. The control group was ageand sex-matched healthy subjects. Demographic data were recorded, and blood was tested for ECLT, PAI-1 level, lipid profiles, fasting blood sugar (FBS), and 4G and 5G polymorphisms of PAI-1 gene. Results: There were 70 subjects participating in this study, consisting of 30 patients and 40 controls. Demographic data, lipid profiles, and FBS were similar between the 2 groups. Furthermore, ECLT and PAI-1 level did not differ between patient and control groups; however, both showed significant correlation (r5.352, P5.006). The 4G/5G polymorphism was the most common genotype in both patient and control groups (69.0% vs. 80.0%). However, 4G and 5G polymorphisms of PAI-1 gene did not correlate with PAI-1 level in this study (P 5 .797). Conclusions: The PAI-1 level and 4G/5G polymorphism may not be a risk factor of AIS in this population. It was also found that the 4G/5G polymorphism was the most common PAI-1 genotype in this study.